Design, Synthesis, Experimental and Theoretical Characterization of a New Multitarget 2-Thienyl-N-Acylhydrazone Derivative - Isadora T. S. Bastos; Pedro de Sena M. Pinheiro; Fanny N. Costa; Miguel D. Rocha; Carlos Mauricio R. Sant'Anna; Delson Braz; Everton T. Souza; Marco A. Martins; Eliezer J. Barreiro; Fabio F. Ferreira; Regina C. Barroso; Carlos A. M. Fraga (MDPI AG, 2018)
Pulmonary arterial hypertension (PAH) is a chronic cardiovascular disease that displays inflammatory components, which contributes to the difficulty of adequate treatment with the available therapeutic arsenal. In this context, the N-acylhydrazone derivative LASSBio-1359 was previously described as a multitarget drug candidate able to revert the events associated with the progression of PAH in animal models. However, in spite of having a dual profile as PDE4 inhibitor and adenosine A2A receptor agonist, LASSBio-1359 does not present balanced potencies in the modulation of these two targets, which difficult its therapeutic use. In this paper, we describe the design concept of LASSBio-1835, a novel structural analogue of LASSBio-1359, planned by exploiting ring bioisosterism. Using X-ray powder diffraction, calorimetric techniques, and molecular modeling, we clearly indicate the presence of a preferred synperiplanar conformation at the amide function, which is fixed by an intramolecular 1,5-N∙∙∙S σ-hole intramolecular interaction. Moreover, the evaluation of LASSBio-1835 (4) as a PDE4 inhibitor and as an A2A agonist confirms it presents a more balanced dual profile, being considered a promising prototype for the treatment of PAH.